Cardiovascular Diseases in Natural Disasters; a Systematic Review: Cardiovascular Diseases in Disasters - Babaie, Javad; Pashaei asl, Yousef; Naghipour, Bahman; Faridaalaee, Gholamreza (Archives of Academic Emergency Medicine, 2021)
Introduction: As a result of destruction and lack of access to vital infrastructures and mental stress, disasters intensify cardiovascular diseases (CVDs) and hence management of CVDs becomes more challenging. The aim of this study is investigating incidence and prevalence of CVDs, morbidity and mortality of CVDs, treatment and management of CVDs at the time of natural disasters. Methods: In the present systematic review, the articles published in English language until 28. 11. 2020, which studied CVDs in natural disasters were included. The inclusion criteria were CVDs such as myocardial infarction (MI), acute coronary syndrome (ACS), hypertension (HTN), pulmonary edema, and heart failure (HF) in natural disasters such as earthquake, flood, storm, hurricane, cyclone, typhoon, and tornado. Result: The search led to accessing 4426 non-duplicate records. Finally, the data of 104 articles were included in quality appraisal. We managed to find 4, 21 and 79 full text articles, which considered cardiovascular diseases at the time of flood, storm, and earthquake, respectively. Conclusion: Prevalence of CVD increases after disasters. Lack of access to medication or lack of medication adjustment, losing home blood pressure monitor as a result of destruction and physical and mental stress after disasters are of the most significant challenges of controlling and managing CVDs. By means of quick establishment of health clinics, quick access to appropriate diagnosis and treatment, providing and access to medication, self-management, and self-care incentives along with appropriate medication and non-medication measures to control stress, we can better manage and control cardiovascular diseases, particularly hypertension.